Validation of a bitmap of genes involved in cherry fruit cracking by digital PCR and qPCR, suitable for plant breeding - Marlene Santos; Alberto Gila-Navarro; Julia Weiss; Berta Gonçalves; Manuela Matos; Marcos Egea-Cortines (Scientific Reports)
Abstract Fruit cracking is a developmental defect depending on genetic and environmental conditions. Fruit cracking has a negative impact on quality and production. Fruits with cracking cannot be commercialized and enhance pathogen contaminations. Identifying genes as markers may help in breeding and post-harvest treatments. We compared qPCR and dPCR methods using a set of 16 genes that appear to be differentially expressed in the cherry varieties Sweatheart with low cracking and Burlat with high cracking indexes. Differences in absolute transcripts spanned across nearly three orders of magnitude. Overall qPCR and dPCR show a highly significant negative correlation of -0.90. The equation allowed converting Ct values to dPCR copy number. However, copy number in dPCR allow a direct comparison across experiments and transcriptomic analysis. The combination of PaCER1, PaXTH, PaEXP1, PaEXP2, PaKCS6, PaWINA, PaWINB and PaCER3 as an expression bitmap can separate cherry fruits with low and high cracking phenotypes based on gene expression. Our results highlight the importance of the wax biosynthesis and cell wall metabolic pathways in susceptibility to fruit cracking. Furthermore, the newly identified bitmap may be useful to test in other locations and with different varieties.